2020
DOI: 10.1123/jsr.2019-0056
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermography Protocol on Reducing the Incidence of Soccer Injuries

Abstract: Context: Infrared thermography has been used to detect skeletal muscle overload and fatigue in athletes, but its use in injury prevention in professional soccer has not been studied to date. Objectives: To establish a novel injury prevention program based on infrared thermography and to determine its influence on the injury incidence in professional soccer players in the preseason. Design: A cross-sectional, prospective study design was used to compare a conventional injury prevention program (CPP) applied ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 17 publications
1
28
0
4
Order By: Relevance
“…Similar to human studies, 109 times. However, we discuss specific intervention strategies that can be used to temporarily minimise biomechanical and biothermal stresses to the SDFT if subclinical degenerative changes have been detected using appropriate screening protocols.…”
Section: Initial De Tec Ti On Of Subclini C Al S Df T Pathology: E supporting
confidence: 70%
See 1 more Smart Citation
“…Similar to human studies, 109 times. However, we discuss specific intervention strategies that can be used to temporarily minimise biomechanical and biothermal stresses to the SDFT if subclinical degenerative changes have been detected using appropriate screening protocols.…”
Section: Initial De Tec Ti On Of Subclini C Al S Df T Pathology: E supporting
confidence: 70%
“…In the acute phase, tendonitis is identified as a focal 'hot spot', later decreasing in temperature, but remaining elevated during the healing process 102. This technique has already shown promise as an early screening tool in soccer players, whereby IRT detection protocols were implemented during preseason training 109. Early detection of subclinical degenerative changes resulted in reduced incidences of injuries reported, as well as days lost to training due to injury.Routine thermographic evaluation of performance horses may also assist in detecting/preventing injury during training and providing an opportunity for preventative action.…”
mentioning
confidence: 99%
“…However, this study pioneered the investigation of possible relationships among the parameters commonly used for the identification of injury risk factors for the thigh muscles (dynamometric parameters) of soccer players and t skin by IRT of hamstrings and quadriceps. Considering previous reports about the importance of a daily IRT asymmetry assessment in injury prevention [ 17 , 19 , 21 , 22 , 23 ], long-term follow-up studies of athletes using IRT evaluation are encouraged. Finally, based on a recent study [ 44 ], further investigations assessing the skin temperature recovery after a cold stress test could add valuable information to the vascularization status of the region analyzed by infrared thermography.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that bilateral differences greater than 0.5 or 0.7 °C have been associated with physiological abnormalities [ 19 , 20 , 21 ]. In the sports scenario, IRT assessed at rest has been frequently used to pinpoint the injury location through skin temperature asymmetries [ 19 , 22 , 23 ], which could be mainly associated with inflammation or alteration of blood perfusion processes [ 17 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the neuromuscular activity during exercise is often used to estimate adaptations, in recent years, growing interest has arisen in the use of infrared thermography to record information during exercise and to evaluate acute responses [ 13 , 14 ]. Skin temperature has become popular in sports and clinical contexts with the aim of predicting the risk of injury [ 15 , 16 ]. The relationship between neuromuscular activation and skin temperature remains unclear.…”
Section: Introductionmentioning
confidence: 99%